Effect of Montmorillonite Addition on The Thermal Resistance Properties of Polyvinyl Acetate - Muchammad Izzuddin Jundullah Hanafi (Jurnal Sains dan Seni ITS, 2016)
PVAc emulsion polymerizations from PVA and VAMthrough semibatch method have been studied. Thepolymerization used DMSO as solvent with montmorillonitefiller of 1%, 2%, and 3% addition. The results of analysisusing FTIR spectorcopy show that industrial, solvent basedPVAc has similar functional group with the PVAc synthesized.Thermogravimetric Analysis (TGA) characterization showsthat industrial, solvent based PVAc has the best thermaldecomposition than the other PVAc synthesized, which is76,16% at temperature of 280-380°C and 22,37% attemperature of 400-500°C.